2007
DOI: 10.1590/s0103-21002007000400015
|View full text |Cite
|
Sign up to set email alerts
|

Pressão arterial de crianças e adolescentes de uma escola pública de Fortaleza - Ceará

Abstract: Objective: To analyze the evolution of systolic blood pressure (SAP), diastolic blood pressure (DAP) and anthropometric measurement values of children and teenagers who presented altered arterial pressure on a first evaluation. Methods: Follow-up study, performed from October / 2004 to December / 2005, at a public school in Fortaleza. One hundred fifty-one subjects between six and seventeen years old were accompanied and evaluated for a period of one year. Results: It was observed that the SAP and DAP of child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…In the present study, as well as in the study by Araujo et al 26 , the variables weight, BMI and AC were positively and significantly associated with BP levels. This fact reinforces the importance of measuring these indicators to detect hypertension and future cardiovascular risks.…”
supporting
confidence: 84%
“…In the present study, as well as in the study by Araujo et al 26 , the variables weight, BMI and AC were positively and significantly associated with BP levels. This fact reinforces the importance of measuring these indicators to detect hypertension and future cardiovascular risks.…”
supporting
confidence: 84%
“…As many other studies show, the male adolescents presented higher levels of SAP and DAP and were more affected by the problem of elevated arterial pressure (3,5,7) . However, there are authors who have not observed any association between arterial pressure and gender among children and adolescents (14)(15) .…”
Section: Discussionmentioning
confidence: 55%
“…It is believed that this discrepancy lies in the fact that they were also based on a single evaluation of arterial pressure. However, authors of a study in which measurements were performed over six visits that occurred during one year, found that the SAP and DAP of children and adolescents decreased throughout the evaluations (5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations